PETANI TANGGUH LERENG MERAPI: (Studi Partisipasi Warga Dalam Rehabilitasi Bencana Erupsi Merapi 2010 - , ALAM SURYA GUMILANG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Merapi eruption in 2010 caused damage to the environment, due to volcanic ash devastated posed capable of settlements and agricultural land as the backbone of the economy of the people. This research aims to reveal knowledge systems of the society vegetable peasant in conducting agricultural rehabilitation programs, as well as to understand their level of success in adapting to the environment that is susceptible to eruptions of Mount Merapi. Research about knowledge system considered to be very important, in order to understand their feelings and thoughts in representing the culture of the social environment, culture, and natural environment, particularly in Gowok Sabrang, Sengi Village, Dukun Sub-district, Magelang Regency, Central Java Province. To achieve the objectives, this research applies a participant observation methods to directly capture socio-cultural phenomenon in local society. In addition, indepth interview is also used by applying a structured interview method (guide interview) that has been prepared in the form of interview guide. The results of this research indicate that changes in farming patterns, such as the use of post-eruption cultivate a patch of land, intercropping and planting pattern with a short harvest period, as well as the efficiency of the treatment plant production costs, making the farmer is able to bounce back to normal activities. The pattern of agricultural production cost savings made by residents after the eruption of this kind continue to be done, and eventually each resident proved able to add some plot land is state of the economy, which means they get better. Kesuksesan warga, merehabilitasi pertanian pasca erusi tersebut, sudah pasti tidak dapat dilepaskan dari berbagai bantuan, dan yang lebih utama adalah kemadirian dari warga sendiri. Sikap kebersamaan, kerja keras, pantang menyerah serta egaliteren merupakan fondasi utama yang terbukti mampu menghadapi bencana erupsi Merapi. Makna yang dapat dipetik dari fenomena ini adalah bahwa, tinggal dan menggantungkan hidup di daerah rawan bencana sungguh sangat beresiko, namun dengan strategi adaptasi yang tepat, bencana tidak harus dipandang sebagai ancaman, karena bisa dieliminir. Success peasant rehabilitating the agricultural post eruption, certainly can not be separated from a variety of assistance, and that is more important is autonomy of its own peasant. The attitude of togetherness, hard work, never give up and egaliteren are the main foundation that proved capable of facing the Merapi eruption. Meaning that can be gleaned from this phenomenon, living and livelihood in disaster-prone areas is extremely risky, but with appropriate adaptation strategies, disaster should not be viewed as a threat, because it can be eliminated.